Antigenic analysis of M. paratuberculosis strain TEPS by SDS-PAGE and two-dimensional immunoelectrophoresis - GOSWAMI, T K; JOARDAR, S N; RAM, G C (The Indian Journal of Animal Sciences, 2014)
Mycobacterial antigens are usually complex in nature. Immunoelectrophoretic technique may not be efficient in separation of such complex antigens owing to poor resolving efficacy. In this report, protein components of Ai. paratuberculosis were resolved into 40 polypeptide fractions by SDS-PAGE as detected by Coommassie brilliant blue staining whereas only 8 bands were detected by periodic acid schiff's staining. On crossed immunoelectrophoresis, sonicate an tigen of M. paratuberculosis with hyperimmune goat sera has shown more than 18 immunogenic precipitation lines suggestive of their immunodominant nature.